Community participation in development of cultural village: Study in Bena Baru cultural village, Sambaliung District, Berau Regency, Indonesia - Darmawan Surya Saputra; Ahmad Hidayah; Rianda Abdi; Afdil Hafidh; Muhammad Arifin (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
Community-based tourism has become an important approach to sustainable cultural tourism development by emphasizing active local community involvement in tourism governance. However, previous studies indicate that participation in cultural tourism often remains consultative, while strategic decision-making is dominated by governments and external actors. Research examining indigenous participation in cultural tourism governance through a critical participation perspective remains limited, particularly among indigenous communities in Kalimantan, Indonesia. This study analyzes indigenous community participation in the development of Bena Baru Cultural Village, East Kalimantan, using Arnstein’s Ladder of Citizen Participation as an analytical framework. A descriptive qualitative approach was employed through in-depth interviews, observation, and documentation involving village officials, customary leaders, community leaders, youth groups, artists, and members of the Dayak Kenyah Badeng indigenous community. The findings indicate that participation is concentrated at the levels of manipulation, informing, consultation, and placation, reflecting a tokenistic pattern. Although indigenous communities are involved in deliberative forums, cultural activities, and tourism programs, their influence over strategic planning, budgeting, and policy formulation remains limited. Tourism governance is further shaped by top-down planning, weak participatory institutions, and unequal power relations between government actors and indigenous communities. Theoretically, this study contributes to community participation and Community-Based Tourism literature by demonstrating the relevance of Arnstein’s framework for understanding indigenous participation in cultural tourism governance. Practically, it highlights the need to strengthen collaborative governance mechanisms to enable more meaningful indigenous participation in sustainable cultural village development.